Gambaran Pengetahuan Ibu Sesudah Diberikan Pendidikan Kesehatan Tentang Imunisasi DPT Di Puskesmas Ciptomulyo Kota Malang - Magdalena Putri; Goretti Maria Sindarti (Poltekkes Kemenkes Malang, 2020)
Health education is an experience that is useful in influencing the habits, attitudes and knowledge of a person or society. Health education is given by extension methods and given repeatedly to remember and so that the subject is more familiar with the material that has been provided by the researcher. This will increase the knowledge of the first subject and the second subject to be very well proven by delivering their children immunizations, but only the provision of health education is different, for the first subject it is done four times and for the second subject it is done three times because of the perception and mindset that are not the same. The purpose of this study was to describe the knowledge of mothers after being given health education about DPT immunization. Data collection techniques using interviews and documentation with the instruments that have been prepared. The data analysis technique is presented in a narrative form. The results of the study were obtained from the two research subjects. After health education was carried out, the knowledge was better. The conclusion of the two research subjects with the provision of health education can increase knowledge and change bad behavior to be good. Recommendations for future researchers are expected to be able to take more subjects and provide health education with other immunization topics.